2019
DOI: 10.1016/j.heliyon.2019.e01926
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pozzolanic and filler effect of rice husk ash on the mechanical properties and microstructure of brick aggregate concrete

Abstract: The aim of this study was to investigate the pozzolanic effect (PE) and filler effect (FE) of rice husk ash (RHA) on the mechanical properties and microstructure of brick aggregate concrete (BAC). For this, concrete cylinders (100 mm × 200 mm) were prepared with 0–25% RHA with water-to-binder ratios of 0.50 at a constant mix-ratio of 1:1.5:3 and cured in water. Test results revealed that the mean particle size of RHA decreases with increasing grinding time. The compressive strength ( ) of BAC due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…The next image on the right shows different colors denoting every single pore which generates the next pore size segmental image on the right. The pore space segmentation characterization is an important method to understand the mechanical properties of concrete [35,[59][60][61][62][63]. Table 8 shows the output of MATLAB Analysis of different images of NS and RHA.…”
Section: Original Image Binary Segmentationmentioning
confidence: 99%
“…The next image on the right shows different colors denoting every single pore which generates the next pore size segmental image on the right. The pore space segmentation characterization is an important method to understand the mechanical properties of concrete [35,[59][60][61][62][63]. Table 8 shows the output of MATLAB Analysis of different images of NS and RHA.…”
Section: Original Image Binary Segmentationmentioning
confidence: 99%
“…Type-I ordinary Portland cement (OPC) was used in this experiment [ 21 ]. In addition, blast furnace slag (BFS) and silica fume (SF) were used to give a filler effect for increasing the strength of concrete [ 22 , 23 ]. The 100 MPa of concrete was used in this experiment.…”
Section: Materials and Experimental Programmentioning
confidence: 99%
“…Research [13] of the pozzolanic effect and the filler effect of the rice husk ash on the mechanical properties and microstructure of a brick aggregate concrete showed that the compressive strength, due to filler effect, are 58.56 -94.62 % less compared to the pozzolanic effect for the 10 -25 wt. % replacement of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength and flexural strength of the brick aggregate concrete due to the pozzolanic effect are 60 -150 % and 25 -150 % higher than that of the filler effect for the 10 -25 wt. % replacement of cement, respectively [13].…”
Section: Introductionmentioning
confidence: 99%